THE CORRELATION BETWEEN MATERNAL HIGH-RISK AGE AND MATERNAL ANXIETY LEVELS DURING PREGNANCY - Novi Yulianti; Hafizah Che Hassan (MEDIS: Jurnal Riset Ilmu Kesehatan, 2024)
Background: High-risk pregnancy is a condition that can affect the state of the mother and fetus in the pregnancy at hand. In primigravida, mental readiness is still significantly lacking in the age of ≤20 years, so in the face of labor is not yet steady. Primigravida with age ≥35 years physically, the risk of complications is greater, but for mental preparation is more prepared. Social support can have a positive impact on maternal anxiety so poor support can affect the anxiety of pregnant women. Objective: This study aims to determine the relationship between the high-risk age of mothers with the level of maternal anxiety during pregnancy. Methods: Quantitative research with cross-sectional correlation analytic design. The sample in this study was 30 pregnant women who performed pregnancy checks at PMB Suratmi Kota Batam with a total sampling technique. Data analysis using chi-square test. Data collection using the Rating Scale for Anxiety (HaRS) questionnaire. Results: The results of this study showed that the age variable of pregnant women aged ≤20 years was 21 people (70.0%), and pregnant women ≥35 years were 9 people (30.0%) with high risk. Anxiety variables from 30 pregnant women: Most of the 15 people (50.0%) experienced moderate anxiety, 5 people (16.7%) experienced mild anxiety, 8 people (26.7%) experienced severe anxiety, and those who did not experience anxiety were 2 people (6.7%). The relationship between high-risk age and the level of maternal anxiety during pregnancy at PMB Suratmi Batam City, the p-value=0.002 <α 0.05. Conclusion: There is a significant relationship between the